Language Learning Autonomy and Action Research - M.V. Joyce Merawati (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2016)
This study attempts to explore the development of learning autonomy of seventeen Civil Engineering students at a state polytechnic in Indonesia when learning English as a foreign language by conducting inductive action research together with the students and was supported by the managing staff of Self-Access Language Learning (SALL). The development was analyzed from learners’ journals, observations, and class discussion or small talks. The results showed that conducting action research with the students for two semesters develops language learning autonomy in various degrees moving from physical to cognitive behaviors.